Preference nezletilého pacienta při poskytování zdravotních služeb – právní a etický pohled (Paliativní medicína, 2023)
The decision-making process to provide health services to adolescent patients brings about specific issues. One of these is the legal and ethical requirement that the patient's opinion be given relevant weight in the decision as to what health services will or will not be provided to them. As with adult patients, the interests, values and preferences of the minor patient may clash with the wishes of the care team or its individual members. In such a situation, it is important to clarify whose values and preferences are fundamental to the decision and how to reach that conclusion. This article outlines the basic legal and ethical considerations involved in the specific case of making decisions about providing care to an adolescent patient. The aim of the article is to present a case study to illustrate how legal and ethical reasoning can be constructed in a way that is understandable and useful for clinical practice.